The Role of Posyandu Cadres in Reducing Malnutrition Rates (Stunting) in Toddlers in Belawan Sicanang Village, Medan Belawan District - Anjani, Putri; Nainggolan, Elizon (Journal of Nonformal Education and Community Empowerment, 2025)
This study aims to analyze the role of Posyandu cadres in reducing malnutrition (stunting) among toddlers in Belawan Sicanang Village, Medan Belawan District. Thus, the research method used in this study is a qualitative descriptive approach. Data were generated and obtained through observation, interviews, and documentation. The results of the study illustrate that Posyandu cadres are central actors in mobilizing the community to be aware and care about health, especially in the implementation of Posyandu. They are not only implementers of activities, but also motivators, educators, and role models in the community. The success of the Posyandu program depends heavily on the consistency, communication skills, and dedication of the cadres in establishing good relationships with residents. There are several factors supporting the role of cadres in community empowerment, including: social closeness of cadres with the community, collaboration with community health centers and community leaders, and the availability of communication media. There are several factors inhibiting the role of cadres in community empowerment, such as: low health literacy, limited access and geographical conditions, and limited roles due to social relationships.